Pembangunan Ekonomi dalam Perspektif Islam - Retnawati Siregar; M. Shabri Abd. Majid (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Economic growth and development are the most common components in economic policy strategies, but as countries develop and progress, on the other hand, poverty rates are increasing dramatically and have various kinds of problems in other economic sectors. The purpose of this study is to discuss issues that occur in Islamic-based economic expansion. By examining growth and development which includes how economic development is to build the welfare of the people, how to increase human resources, and how the role and responsibilities of the state in Islam are. This research method uses a research library and uses descriptive analysis. The results of this study indicate that the issue of economic growth and development has become a point of interest for experts in Islamic economic studies. Most of the direct economic growth and development, summarized in the teachings of the Qur'an, Sunnah, and previous Islamic thinkers. It has become a very serious focus point on increasing the welfare of the ummah, human resources and innate capacity to improve the position of human dignity and status which is emphasized on the growth and development of the Islamic economy, and the role and responsibility of the state in Islam.